Designing an Integrated Information System for Collaborative Quality Assurance in Early Childhood Education: A Systematic Literature Review - Saugi, Wildan; Azainil, Azainil; Haeruddin, Haeruddin; Buhari, Muhammad Ramli (UIN Sultan Maulana Hasanudin Banten, 2025)
This study aims to identify and analyze the design of an integrated information system that supports the quality assurance of early childhood education (PAUD) collaboratively. Using a Systematic Literature Review (SLR) approach, the study screened and examined 12 scientific articles from the Scopus database published between 2015 and 2025. The study process follows the PRISMA 2020 guidelines with the stages of identification, screening, feasibility assessment, and inclusion. The results of the thematic analysis show five main themes in the integration of the quality and information system of early childhood education, namely: institutional technical efficiency, information security and risk management, documentation social practices, institutional collaboration, and ethical and environmental dimensions. This study found that most PAUD information systems are still administrative and do not fully support participation, pedagogical reflection, and collaborative governance. This research contributes to the development of an integrative, participatory, and contextual information system-based quality management model of early childhood education. These findings are expected to serve as a basis for policy and practice development at the institutional and government levels, as well as open up space for further research based on local implementation.